Defining the feasibility of same day adrenalectomy - A prospective matched cohort study - Gabriele Galata', FRCS, MD; Katerina Alexandrou, MD; Nadia Talat, BSc (hons); Helena Hanschell, MD; Ammar Al-Lawati, MD; Patrick Klang, MD; Assef Jawaada, MD; Fraser Dunsire, FRCA, MD; Johnathan Hubbard, FRCS, MD; Dylan Lewis, FRCR, MD; Simon Aylwin, FRCP, MD; Klaus-Martin Schulte, FRCS, FRACS, MD (Surgery Open Science, 2023)
Background: Despite technical advances, day surgery still accounts for <1 % of adrenal procedures. We investigated feasibility and safety of same day adrenalectomy (SDA). Methods: Between We recruited 30 patients with primary hyperaldosteronism (PHA) or Cushing's syndrome (CS) into a prospective matched, single centre cohort study to evaluate the impact of exposure to a same day discharge pathway (SDA cohort; n = 10) or inpatient adrenalectomy (PIPA cohort; n = 20). We compared results to a matched cohort (n = 40) from our prospective in-patient adrenalectomy registry (RIPA cohort). Results: Mean age was 51.3 ± 8.5 years, with 43 % female, 3.3 % ASA I and 96.7 % ASA II. Lesion size was 17 ± 9 mm (range 5-40 mm). 80 % of patients presented with PHA. The predefined primary endpoint (discharge on same calendar day without major complications, emergency presentation or readmission) was achieved in 100 % of SDA, but none of the in-patients (χ2 = 57; p < 0.0001). The secondary endpoint (discharge within 23 h of surgery without major complications, emergency presentation or readmission) was achieved in 100 % of SDA, 90 % of PIPA (n.s.), 33 % of RIPA (33 %; χ2 = 14.6 p < 0.001), and 51.5 % of IPA patients (χ2 = 8.5 p < 0.01). Combining SDA and PIPA cohorts, 93.3 % of treatment episodes met widely used (WHO, United States) definitions of day surgery as completion of the hospital care episode within 23 h. Patients admitted for SDA were highly satisfied (100 %). Conclusion: Same day discharge after adrenalectomy is feasible, safe, and well-perceived in appropriately selected patients with PHA and Cushing's syndrome.